Flexible antenna design for wearable telemedicine applications - Fatah, Sara Yehia Abdel; Taher, Fatma; Elwi, Taha A.; Sree, Mohamed Fathy Abo; Alibakhshikenari, Mohammad; Virdee, Bal Singh; Livreri, Patrizia; Parchin, Naser Ojaroudi; See, Chan Hwang; Pau, Giovanni; Dayoub, Iyad; Limiti, Ernesto (2023)
In this article, an antenna design is presented based on three horizontally staggered microstrip lines for wearable telemedicine devices. The antenna is excited through a 50-ohm microstrip line. The proposed antenna was fabricated using conductive copper tape of 35µm thickness and printed on a flexible photo paper suitable for telemedicine applications. The proposed antenna has physical dimensions of 40×35×0.635 mm3. It was designed to operate at the ISM band 2.45 GHz. The proposed antenna design was simulated and optimized using Computer Simulation Technology of Microwave Studio Software (CSTMWS). The design of the antenna was then validated through measurement. The results show good agreement between the simulated and measured results. The proposed antenna’s performance is evaluated in terms of radiation efficiency, radiation patterns, and return loss. The results confirm the antenna described here is suitable for wearable wireless electronic devices.